Pengaruh Persepsi Harga Dan Nilai Pelanggan Terhadap Minat Beli Pakaian Pada Distro Naruto Jati Kota Pariaman - Syukrial, Syukrial; Salfina, Lili (Universitas Sumatera Barat, 2021)
The purpose of this study was to examine simultaneously and partially the effect of price perceptions and customer value on buying interest in clothing at Distro Naruto Jati Pariaman City. The method used in this research is quantitative and the population in this study are consumers who shop at Distro Naruto Jati Pariaman City. The sample used was 100 respondents. The data collection technique used a questionnaire, while the data analysis method used multiple linear regression, namely Y = 4.141 + 0.631X1 + 0.289X2 using SPSS Statistics 23. Based on the results of this study, it is hoped that this research can provide material for consideration in determining price perception policies and customer value so as to increase buying interest. Based on the results of this study, it shows that the price perception variable has an effect on consumer buying interest in Distro Naruto Jati Kota Pariaman. The customer value variable also affects consumer buying interest in Distro Naruto Jati Pariaman City. The results of the study simultaneously show that the variables of price perception and customer value have an effect on consumer buying interest in Distro Naruto Jati Pariaman City. And the results of the R Square coefficient of determination test (79.4%) the remaining (20.6%) is influenced by other variables outside the study.